Praktik Akuntansi dan Akuntabilitas yang Sederhana, namun Penuh Makna: Studi Fenomenologi pada Pengempon Pura Beji Sangsit - Dharmawan, Nyoman Ari Surya; I Nyoman Putra Yasa; Wiguna, I Gd Nandra Hary (Universitas Pendidikan Ganesha, 2024)
This research is motivated by the existence of religious organizations, namely pura (Hindu temples), which play a central role in the social order of Balinese society. The study aims to explore the meaning of accounting and accountability as practiced by the pengempon (temple caretakers) of Pura Beji in Sangsit Village. This study employs a qualitative approach with Husserl’s transcendental phenomenology as the analytical framework. Data were collected through three techniques: interviews, observations, and documentation. The data analysis process consisted of epoche, phenomenological reduction, imaginative variation, and the synthesis of meaning and essence. The findings reveal that accounting and accountability carried out by the pengempon are manifested in the form of financial records and memory. In this case, the caretakers prefer to rely on memory rather than written records. The meaning embedded in their accounting practices reflects a focus on fulfilling internal informational needs about activities and operations. This also suggests that accounting and accountability are practiced according to the needs and capabilities of the implementers.